Case report: Stereotactic body radiation therapy with 12 Gy for silencing refractory ventricular tachycardia - Huang, Shan-Hui; Wu, Yen-Wen; Shueng, Pei-Wei; Wang, Shan-Ying; Tsai, Meng-Chieh; Liu, Yuan-Hung; Chuang, Wen-Po; Lin, Heng-Hsu; Tien, Hui-Ju; Yeh, Hsin-Pei; Hsieh, Chen-Hsi (Frontiers in Cardiovascular Medicine, 2022)
Background Encouraging results have been reported for the treatment of ventricular tachycardia (VT) with stereotactic body radiation therapy (SBRT) with 25 Gy. SBRT with 12 Gy for refractory VT was designed to reduce long-term cardiac toxicity. Methods Stereotactic body radiation therapy-VT simulation, planning, and treatment were performed using standard techniques. A patient was treated with a marginal dose of 12 Gy in a single fraction to the planning target volume (PTV). The goal was for at least ≥ 95% of the PTV to be covered by at least 95% of 12 Gy radiation. Results From April 2021 through June 2022, a patient with refractory VT underwent treatment. The volume for PTV was 65.8 cm3. The mean radiation dose administered to the heart (the heart volume excluding the PTV) was 2.2 Gy. No acute or late toxicity was observed after SBRT. Six months after SBRT, the patient experienced new monomorphic right ventricular outflow tract (RVOT) VT. Interestingly, the substrate of the left ventricular basal to middle posteroseptal wall before SBRT was turned into scar zones with a local voltage < 0.5 mV. Catheter ablation to treat RVOT VT was performed, and the situation remains stable to date. Conclusion This study reports the first patient with refractory VT successfully treated with 12.0 Gy SBRT, suggesting that 12 Gy is a potential dose to treat refractory VT. Further investigations and enrollment of more patients are warranted to assess the long-term efficacy and side effects of this treatment.